Analysing the role of religious education: changes in personality wellbeing among people affected by flood disaster - Yaakub, Muhamadul Bakir; Othman, Khatijah; Nik Nazli, Nik Nadian Nisa (Universiti Utara Malaysia, 2018)
This study investigates the relationship of trauma events towards perceived knowledge, religious personality and well being. Structural Equation Modelling - Partial Least Squares methodology was used to assess the hypothesized model that linked all the constructs of trauma events and perceived knowledge with the religious personality and well-being. The questionnaire was adopted from the previous study and distributed to flood victims at Kelantan and Terengganu. From the analysis, it reveals that all the relationships in the hypothesized model were significant and this shows that all constructs of trauma events, perceived knowledge, religious personality and well-being a vital role in religious education statistics.